Digital governance transformation in retail MSMEs: an agile administration and omnichannel excellence integration model - Rahayu Tri Utami; Susbiyantoro; Edy Sambodja; Farida Frihatini (Universitas Negeri Surabaya, 2026)
Digital transformation has become a strategic necessity for retail micro, small, and medium enterprises (MSMEs) amid intensifying digital market competition; however, many MSMEs adopt digital technologies without strengthening structured governance and administrative systems, resulting in fragmented and unsustainable digital initiatives. This study aims to examine the roles of Digital Governance Effectiveness and Agile Administration in shaping Omnichannel Excellence and to analyze their impact on MSME performance and competitiveness. A quantitative confirmatory research design was employed, involving 120 retail MSME owners and managers who have adopted at least one digital channel, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that Digital Governance Effectiveness significantly enhances Omnichannel Excellence, Agile Administration improves organizational responsiveness and adaptability, and Omnichannel Excellence positively influences MSME performance and competitive advantage. These findings imply that successful digital transformation in retail MSMEs depends not only on technological adoption but also on structured digital governance mechanisms and agile administrative capabilities to ensure sustainable performance. This study contributes to the development of a governance-based digital transformation framework and provides practical insights for MSMEs in designing integrated and sustainable digital strategies.